Inhibition of sodium-proton-exchanger subtype 3-mediated sodium absorption in the gut: A new antihypertensive concept. (August 2020) - Linz, Benedikt; Saljic, Arnela; Hohl, Mathias; Gawałko, Monika; Jespersen, Thomas; Sanders, Prashanthan; Böhm, Michael; Linz, Dominik
Abstract: Arterial hypertension is one of the main contributors to cardiovascular diseases, including stroke, heart failure, and coronary heart disease. Salt plays a major role in the regulation of blood pressure and is one of the most critical factors for hypertension and stroke. At the individual level, effective salt reduction is difficult to achieve and available methods for managing sodium balance are lacking for many patients. As part of the ingested food, salt is absorbed in the gastrointestinal tract by the sodium proton exchanger subtype 3 (NHE3 also known as Slc9a3), influencing extracellular fluid volume and blood pressure. In this review, we discuss the beneficial effects of pharmacological inhibition of NHE3-mediated sodium absorption in the gut and focus on the effect on blood pressure and end-organ damage.